Maximum lifespan and brain size in mammals are associated with gene family size expansion related to immune system functions - Huseyin Kilili; Benjamin Padilla-Morales; Atahualpa Castillo-Morales; Jimena Monzón-Sandoval; Karina Díaz-Barba; Paola Cornejo-Paramo; Orsolya Vincze; Mathieu Giraudeau; Stephen J. Bush; Zhidan Li; Lu Chen; Evangelos Mourkas; et al. (Scientific Reports)
Abstract Mammals exhibit an unusual variation in their maximum lifespan potential, measured as the longest recorded longevity of any individual in a species. Evidence suggests that lifespan increases follow expansion in brain size relative to body mass. Here, we found significant gene family size expansions associated with maximum lifespan potential and relative brain size but not in gestation time, age of sexual maturity, and body mass in 46 mammalian species. Extended lifespan is associated with expanding gene families enriched in immune system functions. Our results suggest an association between gene duplication in immune-related gene families and the evolution of longer lifespans in mammals. These findings explore the genomic features linked with the evolution of lifespan in mammals and its association with life story and morphological traits.